Atratividade e consumo foliar por adultos de Diabrotica speciosa (Germ.) (Coleoptera: Chrysomelidae) em diferentes genótipos de abóbora - Baldin, Edson L. L.; Lara, Fernando M. [UNESP] (My University, 2001)
Some chrysomelids attack the squash from germination to harvest, destroying leaves and causing characteristical damage. Aiming to select squash genotypes less preferred by Diabrotica speciosa (Germar), assays with seedlings and leaf disks were performed at greenhouse and laboratory conditions. Initially, the attractiveness of thirty-three Cucurbita moschata genotypes and one C. maxima genotype (Exposição) was evaluated, the former used as a standard susceptible genotype. Free and no choice tests were performed with eight genotypes selected previously to evaluate seedlings and leaf disks consumption and attractiveness. The index of attractiveness indicated BRA003531 as the most attractive genotype, comparatively to the standard susceptible one. In free choice test for seedling consumption, BRA014869 was the genotype most preferred by adults of D. speciosa, although no significant differences with the control genotype were detected. BRA014958 was the most consumed genotype both in no choice test with seedlings and in free choice test with leaf disks; no choice tests with leaf discs, however, showed no differences on leaf consumption among the genotypes. All genotypes were as suscetible as the standard genotype, and the occurrence of non-preference for feeding as a resistance mechanism was not detected.
Attractiveness and leaf consumption by adults of Diabrotica speciosa (Germ.) (Coleoptera: Chrysomelidae) in different squash genotypes
Keywords: Cucurbitaceae; Feeding preference; Host plant resistance; Insecta